Efficacy of Combination Sofosbuvir, Pegylated-Interferon, and Ribavirin for Treatment of Hepatitis C Virus Genotype 1 Infection in Indonesia - Andri Sanityoso Sulaiman; Rino Alvani Gani; Irsan Hasan; Cosmas Rinaldi A Lesmana; Juferdy Kurniawan; Chyntia Olivia Maurine Jasirwan; Kemal Fariz Kalista; Muhammad Yusuf Hanif (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Background: The presence of direct-acting antiviral (DAA) has improved the treatment of HCV infection and making it more preferable than Pegylated-interferon (PegIFN) and Ribavirin (RBV) based treatment. However, treatment with all DAA combination regimen is limited and expensive in low health care affordability country including Indonesia. The appearance of generic sofosbuvir (SOF) facilitate the utilization of SOF plus PegINF with or withour RBV combination. Therefore, in this study we assessed the efficacy of SOF+RBV and SOF+RBV+PegINF combination for treatment of chronic hepatitis C infections patient with genotype 1 in Indonesia.Method: We performed retrospective study comprising 128 patients in Cipto Mangunkusumo Hospital with chronic hepatitis C, genotype 1, infection. 36 patients was treated with PegINF+SOF+RBV and 92 patients was treated with SOF+RBV with the duration of therapy was 12 and 24 weeks in both arms. The primary endpoint was sustained virologic response after treatment completion (SVR12).Results: In the end of treatment, 99.2% patients achieved undetected HCV RNA in 12 weeks and 24 weeks duration of therapy (100% in PegINF+SOF+RBV group and 98.9% in SOF+RBV group). The SVR12 of PegINF+SOF+RBV reach 100% meanwhile The SVR12 of SOF+RBV reach 88%.  No different in SVR12 between cirrhotic and non-cirrhotic patient in PegINF+SOF+RBV group while in SOF+RBV group, the SVR12 was lower in cirrhotic patients (82.9%) compared to non-cirrhotic patients (92.2%). In multivariate analysis, HIV co-infection is associated with lower SVR12 in SOF+RBV group.Conclusion: 12 weeks and 24 weeks of PegINF+SOF+RBV and SOF+RBV is effective in the treatment of genotype 1 chronic hepatitis C infection.